CHILDREN’S LITERATURE IN EMPOWERING CHILDREN CHARACTER BUILDING - Syahruni Junaid (Elite : English and Literature Journal, 2017)
AbstractChildren literature will provide children with the chances to respond to any form of literary works. It can give them ability to appreciate the cultures of their own. In another way, children literature can develop children’s emotional intelligence and creativity, nurture growth as well as their personality and social skill. Literature has been surround the children’s daily life unconsiusly. Therefore, literature itself does not only give pleasure but also influence the children in many things, one of them is their character. Through the stories the children can learn about many traits of character, among others trustworthiness, respect, responsibility, fairness, caring and citizenship, honesty, cooperation, service to others, freedom, responsibility, courage, honesty, and fairness that are served through the characters and characterization created. Literature plays an important role in our lives and character development. Good stories become a part of us. They are also a wonderful opportunity to explore the three components of character: moral knowing, moral feeling, and moral action.AbstrakLiteratur anak-anak akan memberi anak-anak kesempatan untuk menanggapi setiap bentuk karya sastra. Ini bisa memberi mereka kemampuan untuk menghargai budaya mereka sendiri. Dengan cara lain, literatur anak dapat mengembangkan kecerdasan emosional anak dan kreativitas, memelihara pertumbuhan serta kepribadian dan keterampilan sosial mereka. Sastra telah mengelilingi kehidupan sehari-hari anak-anak secara tidak biasa. Oleh karena itu, sastra itu sendiri tidak hanya memberi kesenangan tapi juga mempengaruhi anak dalam banyak hal, salah satunya adalah karakter mereka. Melalui cerita, anak-anak dapat belajar tentang banyak karakter, antara lain kepercayaan, rasa hormat, tanggung jawab, kewajaran, kepedulian dan kewarganegaraan, kejujuran, kerja sama, pelayanan kepada orang lain, kebebasan, tanggung jawab, keberanian, kejujuran, dan keadilan yang dilayani melalui karakter dan karakterisasi dibuat Sastra memainkan peran penting dalam kehidupan dan pengembangan karakter kita. Cerita bagus menjadi bagian dari kita. Mereka juga merupakan kesempatan bagus untuk mengeksplorasi tiga komponen karakter: pengetahuan moral, perasaan moral, dan tindakan moral.